Community‐engaged efforts to increase retention of Black American online registry participants - Miriam T. Ashford; Anna Aaronson; Danqi Zhu; Xinyue Deng; Sandhya Kannan; Catherine Conti; Roxanne Alaniz; Jennefer Sorce; Carole Cypress; Derek Flenniken; Monica Camacho; Juliet Fockler; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Many longitudinal Alzheimer's disease studies fail to retain Black American adults once enrolled. This limits the generalizability of research findings. METHODS The Community‐Engaged Digital Alzheimer's Research (CEDAR) study developed digital, culturally‐informed, community‐engaged efforts to increase longitudinal registry task completion of Black American Brain Health Registry (BHR) participants. Difference‐in‐differences analysis was conducted to compare longitudinal registry task completion rates within groups (before vs. after CEDAR referral) and between groups (enrolled in CEDAR vs. not enrolled). RESULTS Of 3888 invited Black American BHR participants, 420 (10.8%) enrolled in CEDAR. For CEDAR participants, we found significant increases in enrollment rate into referral studies and BHR timepoint completion rate after enrollment into CEDAR. Compared to those not enrolled, CEDAR participants had higher rates of: enrollment in referral studies, timepoint completion, initial questionnaire completion, and neuropsychological test completion. DISCUSSION The results provide preliminary evidence that CEDAR's culturally‐informed, community‐engaged research efforts were effective at improving engagement of Black American adults in an online longitudinal study. This is evidenced by increased registry engagement before and after enrollment and in comparison to Black American BHR participants not enrolled in CEDAR. These results need to be interpreted cautiously due to selection biases. This strategy can be adapted to other studies and settings. Highlights CEDAR is an online AD/ADRD registry engagement intervention for Black participants. The intervention is community‐engaged, digital, culturally‐informed, and multifaceted. Engagement rates increased before versus during the intervention for enrollees. Engagement rates decreased over the same time period for non‐enrolled participants. Results need to be interpreted with caution due to selection biases.